2012
DOI: 10.1016/j.jana.2011.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care Behaviors and Activities for Managing HIV-Related Anxiety

Abstract: The goal of this study was to identify the baseline prevalence and effectiveness of anxiety self-management strategies in a convenience sample of persons living with HIV (PLWH; n = 343) in the United States, Puerto Rico, Kenya, and South Africa who reported HIV-related anxiety symptoms. Relationships between demographics and anxiety characteristics were determined, as was the effectiveness of self-care activities/behaviors to reduce anxiety. We found that the use of anxiety self-management strategies varied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…anxiety and stress). 17,30 In addition to inability to sleep, the aforementioned factors can diminish the quality of sleep resulting experiences of physical and mental fatigue, depression, and excessive daytime sleepiness. 5,28,29 Finally, PLWH may turn to the use of substances or caffeine intake to help them sleep or to cope with fatigue or psychological symptoms, 2 but studies have found that such actions often exacerbate sleep disturbances thus perpetuating fatigue rather than eliminating it.…”
Section: Fatigue In People Living With Hivmentioning
confidence: 99%
“…anxiety and stress). 17,30 In addition to inability to sleep, the aforementioned factors can diminish the quality of sleep resulting experiences of physical and mental fatigue, depression, and excessive daytime sleepiness. 5,28,29 Finally, PLWH may turn to the use of substances or caffeine intake to help them sleep or to cope with fatigue or psychological symptoms, 2 but studies have found that such actions often exacerbate sleep disturbances thus perpetuating fatigue rather than eliminating it.…”
Section: Fatigue In People Living With Hivmentioning
confidence: 99%
“…Reported rates of anxiety symptoms that do not necessarily meet criteria for an anxiety disorder in PLWH are also striking. Forty-four percent of the 1,886 participants with self-reported HIV disease in an international multi-site study conducted by the International Nursing Network for HIV Research indicated that they had experienced anxiety symptoms (Kemppainen et al, 2012). Anxiety disorders have been reported to be highest among groups with the highest HIV prevalence rates, including women of color and men who have sex with men (O'Cleirigh et al, 2009).…”
Section: Prevalencementioning
confidence: 99%
“…Screening for a previous psychiatric history, including a diagnosis of anxiety or depression, and exposure to domestic violence, abuse, or other traumatic events is also important (Basu et al, 2005). Because selfmanagement practices also play a critical role in determining health-related outcomes in HIV disease, providers should assess the use and effectiveness of any strategies used to self-manage anxiety symptoms (Kemppainen et al, 2012).…”
Section: Assessment and Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, building social relationships is a strategy that people living with this disease undertake to manage their mental health issues [7]. Kemppainen et al [55], in a sample of 259 people with HIV, found that talking with family and friends was the most frequently (57%) cited strategy used to manage HIV-related anxiety.…”
Section: Social Facilitation: Social Supportmentioning
confidence: 99%